The corn pollen as a food source for honeybees - doi: 10.4025/actasciagron.v33i4.10553 (Acta Scientiarum. Agronomy, 2011)
This experiment was conducted on the campus of the University Center Moura Lacerda, Ribeirão Preto, in 2009 and 2010 with the objective of verifying the attractiveness of corn pollen for the Africanized honeybees Apis mellifera. The frequency of these bees, and the foraging behavior and stability were obtained by counting the first 10 min. of each hour, from 7.00 to 18.00, on three different days. Africanized honey bees collected only pollen in male flowers of maize, with a peak frequency of 9.00 in 2009 and between 16.00 and 17.00 in 2010. The corn pollen was very collected by Africanized honey bees, an important food source for these bees.